2020
DOI: 10.1007/978-981-15-1580-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Collectins: Innate Immune Pattern Recognition Molecules

Abstract: Collectins are collagen-containing C-type (calcium-dependent) lectins which are important pathogen pattern recognising innate immune molecules. Their primary structure is characterised by an N-terminal, triple-helical collagenous region made up of Gly-X-Y repeats, an a-helical coiled-coil trimerising neck region, and a Cterminal C-type lectin or carbohydrate recognition domain (CRD). Further oligomerisation of this primary structure can give rise to more complex and multimeric structures that can be seen under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 359 publications
(358 reference statements)
0
40
0
1
Order By: Relevance
“…The enrichment of KEGG signaling pathways showed that the relevant action pathways related to the immune system mainly included Toll-like receptor (TLR) signaling, T cell receptor signaling, B cell receptor signaling, and Jak-STAT signaling pathways. Recent studies have shown that innate immunity is an important body immunity, and the pattern recognition receptor fam-ily (PRR) is necessary for the natural immune re-sponse to recognize microbial pathogens; the multiple conservative points of pathogen recognition are called pathogen-related molecular patterns (PAMP) [ 22 ] . TLRs, the first members of the PRR fam-ily widely present in the immune system, can spe-cifically identify pathogenic microorganisms and transmit extracellular antigen recognition informa-tion into cells [ 23 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of KEGG signaling pathways showed that the relevant action pathways related to the immune system mainly included Toll-like receptor (TLR) signaling, T cell receptor signaling, B cell receptor signaling, and Jak-STAT signaling pathways. Recent studies have shown that innate immunity is an important body immunity, and the pattern recognition receptor fam-ily (PRR) is necessary for the natural immune re-sponse to recognize microbial pathogens; the multiple conservative points of pathogen recognition are called pathogen-related molecular patterns (PAMP) [ 22 ] . TLRs, the first members of the PRR fam-ily widely present in the immune system, can spe-cifically identify pathogenic microorganisms and transmit extracellular antigen recognition informa-tion into cells [ 23 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lung surfactant protein (SP)-A and SP-D also belong to the collectin family. However, they do not activate the complement system ( Tenner et al, 1989 ), as reviewed in Murugaiah et al (2020) . The protein CL-12 (also called collectin placenta 1 or CL-P1) may be included in the family ( Hansen et al, 2016 ).…”
Section: Complement Deficiencies and Loss- Or Gain-of-function Mumentioning
confidence: 99%
“…The N-terminal regions have 1–3 cysteine residues that can form disulphide links, cross-linking the collagen regions, which are comprised of three polypeptide chains and can be further organised into large oligomeric structures composed of a maximum of six subunits (Hansen and Holmskov 2002 ). Collectins are soluble pattern recognition receptors (PPRs) specialised at recognising pathogen-associated molecular pattern (PAMPs) of carbohydrate moieties such as lipopolysaccharide (LPS) that are present on microbial surfaces (Janeway 1989 ; Hansen and Holmskov 1998 ; Murugaiah et al 2020 ). Recognition and binding occur via the CRD regions and can lead to pathogen agglutination, neutralization and/or clearance by opsonization of the microbe and recruitment of phagocytes for clearance (Kishore et al 2006 ; Murugaiah et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Collectins are soluble pattern recognition receptors (PPRs) specialised at recognising pathogen-associated molecular pattern (PAMPs) of carbohydrate moieties such as lipopolysaccharide (LPS) that are present on microbial surfaces (Janeway 1989 ; Hansen and Holmskov 1998 ; Murugaiah et al 2020 ). Recognition and binding occur via the CRD regions and can lead to pathogen agglutination, neutralization and/or clearance by opsonization of the microbe and recruitment of phagocytes for clearance (Kishore et al 2006 ; Murugaiah et al 2020 ). Mice engineered to be genetically deficient in SP-A or SP-D showed increased susceptibility to microbial infections (Levine and Whitsett 2001 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation